APOBEC3G genotypes and proviral DNA hypermutations on HIV/AIDS disease progression in Thai and Cambodian children. (December 2015) - Bunupuradah, Torsak; Matsuoka, Kazuhiro; Imahashi, Mayumi; Iwatani, Yasumasa; Ananworanich, Jintanat; Puthanakit, Thanyawee; Saphonn, Vonthanak; Aurpibul, Linda; Sophonphan, Jiratchaya; Yagi, Tetsuya; Phanuphak, Praphan; Sugiura, Wataru
Aim: To evaluate the effect of APOBEC3G host factor on HIV/AIDS progression in perinatally HIV-infected Thai and Cambodian children with distinct clinical patterns; rapid progressors (RPs) and long-term nonprogressors (LTNPs).Materials & methods: APOBEC3G genotypes were determined by polymerase chain reaction-restriction fragment length polymorphism in DNA samples. APOBEC3G-mediated G-to-A hypermutations were analyzed by sequencing of the vif/vpu genes from proviral DNA.Results: Frequency of APOBEC3G 186H/R genotypes, AA:AG:GG, in the RPs was 100:0:0% and 83:17:0% (p = 0.3) in LTNPs. Hypermutation of the vif -coding region was observed in none of the RPs and 8.3% of LTNPs (p = 0.5). Hypermutations at the vpu genes were not detected in either groups' proviral DNA.Conclusion: We observed no significant association of APOBEC3G genotypes and hypermutation rates between children with different profiles of HIV/AIDS disease progression.